A Study on Tourist Perception Towards Usage of Mobile Wallet - et.al, Dr. Pankaj Kumar Tyagi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The digital revolution changed the way this world functions in more ways that anyone could imagine. From being able to buy a small chocolate to paying for cars, almost anything can be bought using a mobile phone, thanks to Mobile Wallets. We are living in extraordinary times where revolution and evolution is rampant. Survival of businesses no longer depends on meeting demand but meeting the demand ensuring itscustomer’s utmost ease. Coming to talk of ease, one of the most revolutionary technologies that has made lives easier is Mobile Wallets and thus, they’ve become a large part of our daily lives. The proposed research aims to study the perception of tourists towards the usage of mobile wallets or Mobile Wallets. The industry of tourism is one of the largest in India, which has contributed more than $247 billion U.S.D to the country’s GDP in 2018-19 (a study by Statista) and is expected to top a whopping $500 billion U.S.D by as close as 2029.Though the recent times have shown signs of a slow economy and post the pandemic, many countries have also declared recession, the tourism industry has shown positive signs and there are no signs of slowing down which means that for the people, it has been creating jobs and thus providing indirect and direct employment.In 2016, post demonetization, usage of Mobile Wallets saw a huge demand. With a cash crunch for 1.3 Billion people, Mobile Wallets & card payments seemed to be the most viable option. Companies like Paytm saw this is an opportunity and cashed in on it. A report by economic times suggested that Mobile Wallet transactions saw 40 times increase in volume in the past five years which is proof that the usage of mobile wallets has indeed increased overtime and why not? Mobile Wallets reduce the hassle of looking for change, they’re a safe way of transacting and given the fact that people are trying to avoid any form of contact, it is a great way to make payments without physically touching anything or anyone.